ANALISIS FENOMENA FEAR OF MISSING OUT SELEBRITI PADA KONSER BLACKPINK JAKARTA DI TWITTER - Tannia, Fennita; Priscillia, Bernice; Scholus, Jessica Elisabeth (Universitas Swadaya Gunung Jati, 2023)
Having a great musical influence, K-pop music is in demand by many international communities, including Indonesia. The large number of fans in Indonesia has made K-Pop industry players vying to hold K-Pop activities such as concerts. The Blackpink concert is one of the biggest concerts in Indonesia in 2023, offering and uplifting the fans. Not only that, the popularity of the Blackpink concert also caused FoMO, especially among celebrities. The FoMO phenomenon in celebrities themselves had angered Blackpink fans by expressing it on social media Twitter and making the issue a trending topic. From the magnitude of the FoMO phenomenon that occurs to these celebrities, this study is entitled